2018
DOI: 10.4196/kjpp.2018.22.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic modification of α-N-acetylgalactosaminidase enhances cisplatin resistance in ovarian cancer

Abstract: Although cisplatin is one of the most effective antitumor drugs for ovarian cancer, the emergence of chemoresistance to cisplatin in over 80% of initially responsive patients is a major barrier to successful therapy. The precise mechanisms underlying the development of cisplatin resistance are not fully understood, but alteration of DNA methylation associated with aberrant gene silencing may play a role. To identify epigenetically regulated genes directly associated with ovarian cancer cisplatin resistance, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Our findings demonstrate its potential to identify treatment sensitivity in asthmatics. Epigenetic therapeutics that selectively target DNA methylation have been shown to increase the effectiveness of existing treatments in the field of cancer biology, and these therapeutics may have applications in other fields and diseases, including asthma . Further research into the identified DNA methylation marks may lead to the discovery of epigenetically mediated pathways of drug resistance and novel epigenetic therapeutics to increase sensitivity to ICS treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings demonstrate its potential to identify treatment sensitivity in asthmatics. Epigenetic therapeutics that selectively target DNA methylation have been shown to increase the effectiveness of existing treatments in the field of cancer biology, and these therapeutics may have applications in other fields and diseases, including asthma . Further research into the identified DNA methylation marks may lead to the discovery of epigenetically mediated pathways of drug resistance and novel epigenetic therapeutics to increase sensitivity to ICS treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetics can play a role in drug sensitivity and resistance . DNA methylation is an epigenetic mechanism that regulates both the activation and silencing of DNA transcription.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last decade, the study of epigenetics in ovarian cancer has gained tremendous attention . Epigenetic modifications like DNA methylation and histone deacetylation lead to cancer progression, metastases, and an increase in chemoresistance in various cancers including ovarian cancer . Unlike genetic mutations that cannot be altered, epigenetically‐induced alterations are hopeful targets and their knowledge has led to the advent of histone deacetylase inhibitors (HDACis) and DNA hypomethylating agents (HMAs) …”
Section: Introductionmentioning
confidence: 99%
“…3 Epigenetic modifications like DNA methylation and histone deacetylation lead to cancer progression, metastases, and an increase in chemoresistance in various cancers including ovarian cancer. [4][5][6] Unlike genetic mutations that cannot be altered, epigenetically-induced alterations are hopeful targets and their knowledge has led to the advent of histone deacetylase inhibitors (HDACis) and DNA hypomethylating agents (HMAs). [7][8][9] Recently, there has been a great interest in understanding aberrant epigenetic events affecting not only the tumor but also its associated microenvironment.…”
Section: Introductionmentioning
confidence: 99%